Essays on agricultural productivity and the impact of food price change on welfare in Africa - Hodjo, Manzamasso (Kansas State University, 2020)
Africa is the most food-insecure continent in the world, according to the World Bank and the United Nations Food and Agricultural Organization. While low purchasing power is the main cause of food insecurity, inefficient domestic food production is also a major constraint. Our study specifically focused on four food production issues in Africa, namely, agricultural productivity, cropland use, food demand and welfare analysis, and demand-led crop breeding. First, we assessed the impact of public spending on agricultural productivity in Africa. We estimated the effect of two government-spending measures: Agriculture Budget Share (BS) and Research Share of Agricultural GDP (RS) on agriculture total factor productivity growth (TFPG). We used a panel fixed-effect estimator to control for the country-specific characteristics of twenty-eight African economies from 1991–2012. Although North African economies appeared to have the highest TFPG, this did not translate into the highest agricultural and research budget share. Meanwhile, Central African economies exhibited the lowest BS and RS, along with the lowest TFPG of the continent. The panel fixed-effect estimator revealed a marginal impact of 6.77% for RS on TFPG after seven years. However, the cumulative marginal impact of BS on TFPG is estimated at 7.21% over the eight years that follow the budget increment. Our findings suggest that a BS of 14% and a RS of 15% are required for a country to double its TFPG in the eight following years. Therefore, additional, and continuous investment in research and development is required for a significant productivity enhancement, especially in Sub-Saharan Africa. Second, we assessed the factors that shape cereal cropland allocation decisions in Nigeria and Niger. We theoretically derived the key cropland allocation arguments using the household model. Next, we used the World Bank LSMS-ISA data to map acreage mean centers and fit a fractional regression model using the panel fixed-effect estimator. We assessed the traditional Mendelsohn land use model and uncovered its limitation in efficiently approximating cereal cropland allocation. We improved the appropriateness of fit of the traditional Mendelsohn model by controlling for additional factors, such as food prices, socio-demographics, and food trade factors. Overall, we found cereal acreage shares in Nigeria and Niger to be spatially heterogeneous and determined by climatic, price, and trade factors. Additionally, farmers tend to base their cropland allocation decisions upon the price of the most important staples: maize in Nigeria; millet and sorghum in Niger. Furthermore, due to their tolerance to heat and drought, sorghum and millet compete for northeast farmland in both countries, especially for rainfed croplands. Thus, our study illustrates that millet and sorghum are key choices in ensuring food security in the context of global warming and rainfall instability. Our findings fill a literature void and provide policy makers with evidence to foster geo-referenced farmer cooperatives aimed at enhancing food production. Furthermore, our findings could be incorporated into a land use framework for planning, environmental monitoring, scenario analysis, and impact assessment. The third essay analyzed the staple foods consumption patterns of households in Niger by estimating a complete demand system. Demand elasticities are estimated using the Niger 2011 and 2014 LSMS-ISA household survey data to fit the modified Linear AIDS model. The results indicated that food consumption patterns in the country are affected by income and prices, as well as by socio‐economic and geographic factors. All food items have positive expenditure elasticities and negative own‐price elasticities, with rice exhibiting the most elastic demand. We found millet to be a necessity while rice and sorghum are luxuries. Additionally, our analysis revealed that urban households had a more diversified staple demand pattern. Furthermore, the welfare analysis revealed that an increase of millet price reduces rural welfare more than an increase in sorghum price. On the other hand, a sorghum price increase adversely affects the welfare of urban households the most. For example, a 20% increase of the millet or sorghum price reduces the average household welfare by 5.88% and 4.38%, respectively. This study highlights the importance of estimating staple food demand elasticities for both research and policymaking during a food price shocks. Our findings revealed that millet price is the canal that might foster support programs targeting the poorest households in Niger. Our fourth and last essay is a theoretical argument for demand-led breeding in a small-scaled farming system. Our investigation stems from the fact that agricultural productivity lags in small-scaled farming in Sub-Saharan Africa. While inadequate production capital, water control and poor infrastructure remain important challenges, the low adoption of improved and high-yielding varieties is a key limiting factor for productivity enhancement. Often, studies elucidating improved technology implementation are focused upon the adoption (demand) rather than the creation (supply). In this analytical essay, we reviewed theoretical causes and solutions to low varietal uptake for sorghum. Consistent with much of the structural research framework, we presented asymmetric information, bounded rationality, and weak intellectual property as key causes of seed market coordination failure. Leaning on the technology adoption under uncertainty model, we showed how market-induced uncertainty, compounded with other factors, reduces farmers’ willingness to trade traditional seeds for improved ones. Furthermore, we used the matching theory, supported with a general equilibrium model, to show how consumer preference drives farm-level adoption. We argued that breeding programs can benefit from effective preference matching across the food value chain while leveraging on the growing demand-led breeding literature. Finally, we presented hypotheses that can be empirically used to assess stakeholders’ weigh and ranking of varietal attributes across the food value chain.
Keywords: Cropland Allocation; Demand-led Breeding; Economic Welfare; Agricultural Productivity; Poverty Reduction